"The Influence of Lifestyle on Consumptive Behavior Among Economics Education Students of the 2019-2020 Cohort - Umasangaji, Anisa; Louhenapessy, William George; Rehatta, Geradin (JENDELA PENGETAHUAN, 2023)
This study aims to determine how to manage village finances through Village Fund Allocation (ADD) and whether it is by the financial management cycle based on the Regulation of the Minister of Home Affairs Number 113 of 2014. The type of research used in this research is descriptive research with a qualitative approach. The subjects in this study were the government staff of Elpaputih Village and the Elpaputih Village Community, who were involved in village development. The data collection techniques used in this study Were interviews and documentation. The results of this study indicate that Elpaputih Village is a village that is in village financial management or Village Fund Allocation Management (ADD) by the Minister of Home Affairs Regulation Number 113 of 2014 regarding Planning, Implementation, Administration, Reporting, and UpcomingAccountanbility because the financial management cycle based on the Ministry of Home Affair number 113 of 2014 is a reference for the Elpaputih Village government in managing village finances of managing village fund allocations